Neurochemical characterization of neurons expressing melanin-concentrating hormone receptor 1 in the mouse hypothalamus() - Chee, Melissa J. S. (2013)
Melanin-concentrating hormone (MCH) is a hypothalamic neuropeptide that acts via MCH receptor 1 (MCHR1) in the mouse. It promotes positive energy balance thus mice lacking MCH or MCHR1 are lean, hyperactive, and resistant to diet-induced obesity. Identifying the cellular targets of MCH is an important step to understanding the mechanisms underlying MCH actions. We generated the Mchr1-cre mouse that expressed cre recombinase driven by the MCHR1 promoter and crossed it with a tdTomato reporter mouse. The resulting Mchr1-cre/tdTomato progeny expressed easily detectable tdTomato fluorescence in MCHR1 neurons, which were found throughout the olfactory system, striatum, and hypothalamus. To chemically identify MCH-targeted cell populations that play a role in energy balance, MCHR1 hypothalamic neurons were characterized by colabeling select hypothalamic neuropeptides with tdTomato fluorescence. TdTomato fluorescence colocalized with dynorphin, oxytocin, vasopressin, enkephalin, thyrothropin-releasing hormone, and corticotropin-releasing factor immunoreactive cells in the paraventricular nucleus. In the lateral hypothalamus, neurotensin but neither orexin nor MCH neurons expressed tdTomato. In the arcuate nucleus, both Neuropeptide Y and proopiomelanocortin cells expressed tdTomato. We further demonstrated that some of these arcuate neurons were also targets of leptin action. Interestingly, MCHR1 was expressed in the vast majority of leptin-sensitive proopiomelanocortin neurons, highlighting their importance for the orexigenic actions of MCH. Taken together, this study supports the use of the Mchr1-cre mouse for outlining the neuroanatomical distribution and neurochemical phenotype of MCHR1 neurons.